2020
DOI: 10.31937/manajemen.v12i1.1578
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Petani Dalam Memilih Platform Crowdfunding (Studi Kasus Pada Petani Hortikultura Di Desa Sumberejo, Magelang)

Abstract: Abstract– Agriculture crowdfunding is a new alternative financing for farmers. The purpose of this paper is to understand some added values provided by agriculture crowdfunding in Indonesia compare to traditional financing and to understand the potential demand of crowdfunding platform. This paper also explores what factors influence farmers to choose crowdfunding platform as their alternative financing. A series of in-depth interview were conducted with 3 Indonesian agriculture crowdfunding s and 30 farmers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…Prioritas terakhir adalah faktor kepastian pasar. Penelitian Pratiwi et al (2020) menyimpulkan bahwa faktor kepastian pasar menjadi alasan petani mememilih platform crowdfunding sebagai salah satu pendanaan alternatif. Faktor kepastian pasar dengan GMk sebesar 0.286.…”
Section: Aspek Pasarunclassified
“…Prioritas terakhir adalah faktor kepastian pasar. Penelitian Pratiwi et al (2020) menyimpulkan bahwa faktor kepastian pasar menjadi alasan petani mememilih platform crowdfunding sebagai salah satu pendanaan alternatif. Faktor kepastian pasar dengan GMk sebesar 0.286.…”
Section: Aspek Pasarunclassified
“…Farmers prefer to access credit from these informal institutions because they are easier to access, do not request for collateral and do not require a long approval process, although these institutions charge higher interest rates compared to banks (Asnawi et al 2018; Supriatna 2008). The study by Supriatna (2008) showed that informal institutions in West Nusa Tenggara, Indonesia, may charge around 24–80% interest rate per year, while the interest rate of People’s Business Credit (Kredit Usaha Rakyat) is 7% per year (Pratiwi et al 2020). Microfinance, crowdfunding and peer-to-peer lending have also emerged as new financial alternatives in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Microfinance, crowdfunding and peer-to-peer lending have also emerged as new financial alternatives in Indonesia. These alternative financing do not request collateral (Khavul 2010; Pratiwi et al 2020) and use a profit sharing mechanism (Pratiwi et al 2020; Widiastuti et al 2018). One agriculture crowdfunding platform offers 70% profit for farmers and 30% profit for investors (Pratiwi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Himpunan Kerukunan Tani Indonesia (HKTI) menyatakan bahwa terdapat lima masalah yang masih menimpa sektor pertanian selama lima tahun kedepan yaitu teknologi, lahan yang semakin sulit, persoalan pupuk, pemasaran dan permodalan. Menurut Van der Meulen dan Van Asseldonk dalam Pratiwi et al, (2020) permodalan dapat digunakan para petani dalam melakukan ekspansi lahan dan investasi dalam menggunakan teknologi.…”
unclassified